2002
DOI: 10.1088/0953-8984/14/22/305
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cd impurity on the electronic properties of CuAlO2 delafossite: first-principles calculations

Abstract: We report on first-principles band-structure calculations of the semiconducting CuAlO2 delafossite compound in the pure form and also with Cd impurity occupying either a Cu or Al position. The computational tool was a full-potential linear augmented plane-wave method, with the generalized gradient approximation accounting for the exchange and correlation effects. The changes caused by the presence of Cd are studied by the analysis of the electronic structure and the electric field gradient (EFG) in both Cd-dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…Several groups theoretically calculated the effects on the electronic behavior of the material due to the presence of various cations in Cu and/or Al sites. Lalić et al [188][189][190] showed that Cd and Zn substitutions on Cu site would produce n-type conductivity in the material, whereas Ni doping in Cu sites would enhance the p-type conductivity of the material. But Cd doping on Al sites would have no effect on the electrical properties of the material.…”
Section: In This Conformation Eight Electrons (Including 2smentioning
confidence: 99%
“…Several groups theoretically calculated the effects on the electronic behavior of the material due to the presence of various cations in Cu and/or Al sites. Lalić et al [188][189][190] showed that Cd and Zn substitutions on Cu site would produce n-type conductivity in the material, whereas Ni doping in Cu sites would enhance the p-type conductivity of the material. But Cd doping on Al sites would have no effect on the electrical properties of the material.…”
Section: In This Conformation Eight Electrons (Including 2smentioning
confidence: 99%
“…[4] we presented band-structure calculations for CuAlO 2 compound with an isolated Cd impurity substituting either Cu (Cd Y Cu) or Al (Cd Y Al) atom. In both cases Cd changes interatomic distances in its neighborhood.…”
Section: Calculations and Interpretation Of The Resultsmentioning
confidence: 99%
“…The task was too complicated to be done directly, by performing the calculations for all compounds, since all of them except the CuAlO 2 are anti-ferromagnets with complicated alignments of magnetic moments (a fact which is difficult to treat accurately in the theory). Instead, we achieved the goal indirectly, in three consecutive steps: 1) by analyzing results of our previous theoretical study of doped CuAlO 2 compound [4] which exhibits an elevated EFG when Cd substitutes the Cu site, and performing some additional EFG decompositions; 2) by calculating EFGs in group of molecules constructed in a way which simulate the Cd neighborhood in delafossites; 3) by calculating electronic structure and the EFG in Cd-doped CuCrO 2 compound, which exhibits the smaller EFG at Cd occupying the Cu site. All calculations were performed using the full potential linear augmented plane wave (FP-LAPW) method [5], as embodied in WIEN2k computer code [6].…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion emerged as a result of series of the first-principles full-potential linear augmented plane wave (FP-LAPW) calculations that we performed for the CuAlO 2 system containing Cd impurities [4], and the Zn or Ni impurities [5] at the Cu position. In this paper we continue to investigate the A site doping effects in the SDOs, but now in their Ag-based branch.…”
Section: Introductionmentioning
confidence: 92%
“…This band is impurity induced, half filled (one electron), and consists mainly of the Cd s and d z 2 , NN O p z and second NN Cu d states. Since its electron density is widely spread over the crystal [4] (Fig. 2b), the electronic structure displays some relevant differences.…”
Section: Cd-doped Compoundsmentioning
confidence: 99%